Synthesis of lead-free Cs4(Cd1−xMnx)Bi2Cl12 (0 ≤ x ≤ 1) layered double perovskite nanocrystals with controlled Mn–Mn coupling interaction. Issue 45 (17th November 2020) - Yang, Hanjun; Shi, Wenwu; Cai, Tong; Hills-Kimball, Katie; Liu, Zhenyang; Dube, Lacie; Chen, Ou
Abstract : Lead-free perovskites and their analogues have been extensively studied as a class of next-generation luminescent and optoelectronic materials. Abstract : Lead-free perovskites and their analogues have been extensively studied as a class of next-generation luminescent and optoelectronic materials. Herein, we report the synthesis of new colloidal Cs4 M(ii )Bi2 Cl12 (M(ii ) = Cd, Mn) nanocrystals (NCs) with unique luminescence properties. The obtained Cs4 M(ii )Bi2 Cl12 NCs show a layered double perovskite (LDP) crystal structure with good particle stability. Density functional theory calculations show that both samples exhibit a wide, direct bandgap feature. Remarkably, the strong Mn–Mn coupling effect of the Cs4 M(ii )Bi2 Cl12 NCs results in an ultra-short Mn photoluminescence (PL) decay lifetime of around 10 μs, around two orders of magnitude faster than commonly observed Mn 2+ dopant emission in NCs. Diluting the Mn 2+ ion concentration through forming Cs4 (Cd1− x Mn x )Bi2 Cl12 (0 < x < 1) alloyed LDP NCs leads to prolonged PL lifetimes and enhanced PL quantum yields. Our study provides the first synthetic example of Bi-based LDP colloidal NCs with potential for serving as a new category of stable lead-free perovskite-type materials for various applications.